"Hungry for Knowledge": Towards a Meso‐History of the Environmental Sciences. Issue 2 (5th September 2019) - Güttler, Nils
Abstract: In recent years, cultural studies and cultural theory have experienced a new wave of ecological thought. Despite the engagement with the Anthropocene the history of ecology and the environmental sciences has remained somewhat of a puzzle. This goes especially for the 20 th century, a period when the sciences of the environment came to matter on a broader scale. Why do we actually know so little about the environmental sciences in the 20 th century? And what could a history of the environmental sciences in that period look like? This article answers these questions with two interrelated arguments. First, by reflecting on different approaches to write the history of ecology since the 1970s, it uncovers crucial entanglements between the history of science and ecological thought that created blind spots regarding the environmental sciences in the 20 th century. Second, it argues for a shift in scales of analysis—towards meso‐scales. With a more regional approach historians can engage with the often‐neglected aspects of the political and economic history of the environmental sciences in the 20th century and thereby also reveal their fundamental infrastructural dimension. Because at its core, the article claims, the environmental sciences were and are essentially infrastructural sciences.